The emotional component of the present-day students’ psychically health: the question analysis - Kichuk, Antonina (Bulletin of Taras Shevchenko National University of Kyiv. Psychology, 2019)
The investigation of the problem of the emotional component of the present-day students’ psychological health is topical in some circumstances. Firstly, the dialectical character of the emotions and feelings correlation, the role of personal feelings in psychological health’s general characteristic. The article also elaborates on the necessity of including the spheres of value and motivation into the overall theoretical and methodological context of discussing the outlined problem. The article also presents the results of empiric studies aimed at investigating the internal organization of the notion of psychological health in students of local universities. The results suggest that students give an exceptional value to the motivational dimension of psychological health. Also, the propositions for the future research in the field of psychological health are outlined. The article also provides a sufficient theoretical review of the notion of psychological health in literary sources. The role of quantitative and qualitative emotional characteristics in personal alteration are important nowadays. The idea of the following theoretical constructs such as "psychological resource" and "psychological health" is investigated. Such principal term as students’ age period in personal skills development, that is defined as an ability "to operate his/her resources" is analyzed. The fundamental psychological researches confirm the importance of the role of the person emotional readiness in his/her development as an "integrated education" which involves not only the psychological health, but also the mental health and spirituality among other components. Such aspect of the problem is investigated in the context of a behavior-oriented approach, where the components are the following: person action that correlate with the phenomenal-emotional manifestation, that is operationalized as the transition of moral sense in philosophy and spiritual dimension.